Dense Crystalline–Amorphous Interfacial Sites for Enhanced Electrocatalytic Oxygen Evolution. (5th November 2021) - Li, Dan; Qin, Yanyang; Liu, Jia; Zhao, Hongyang; Sun, Zongjie; Chen, Guangbo; Wu, De‐Yin; Su, Yaqiong; Ding, Shujiang; Xiao, Chunhui
Abstract: The crystalline‐amorphous (c–a) heterostructure is verified as a promising design for oxygen evolution reaction (OER) catalysts due to the concerted advantages of the crystalline and amorphous phase. However, most heterostructures via asynchronous heterophase synthesis suffer from the limited synergistic effect because of the sparse c–a interfaces. Here, a highly efficient and stable OER electrocatalyst with dense c–a interfacial sites is reported by hybridizing crystalline Ag and amorphous NiCoMo oxides (NCMO) on the nickel foam (NF) via synchronous dual‐phase synthetic strategy. In 1 m KOH, the as‐obtained Ag/NCMO/NF catalyst exhibits a low OER overpotential of 243 mV to attain 10 mA cm −2 and a small Tafel slope of 67 mV dec −1 . Theoretical calculations indicate that the c–a interface can efficiently modulate the electronic structure of the interfacial sites and lower the OER overpotential. Besides, in situ Raman spectroscopy results demonstrate that the c–a interfacial sites can promote the irreversible phase transition to the metal oxy(hydroxide) active phase, and the dense c–a interfaces can stabilize the active phase during the whole OER process. Abstract : Synchronous crystalline–amorphous (c–a) phase synthetic strategy is used to obtain Ag and NiCoMo oxide (NCMO) heterostructure with dense c–a interfacial sites. The resultant Ag/NCMO electrocatalysts exhibit enhanced oxygen evolution activity than the asynchronously synthesized sample with sparse interfacial sites.